Live long and prosper : how Black megachurches address HIV/AIDS and poverty in the age of prosperity theology - Barnes, Sandra L. (Fordham University Press, 2013)
This title offers an intriguing examination of 16 representative black megachurches and explores some of their motivations and subsequent programmatic efforts in light of prosperity or 'health and wealth' theology.